Pengaruh Keputusan Pembiayaan dan Profitabilitas Terhadap Green Accounting - Saragih, Afni Eliana (Universitas Hamzanwadi, 2025)
Environmental issues are pressing and require serious attention, and green accounting emerges as a crucial solution. Examining the influence of financing decisions and company profitability on green accounting is the objective of this research. This study using data from manufacturing companies in the basic and chemical industries listed on the Indonesia Stock Exchange (IDX). Panel data regression analysis is applied to this study as the data is a combination of time series and cross-sectional data. Statistical tests are used to determine whether the Fixed Effect Model, Common Effect Model, or Random Effect Model is the most suitable model for the data before conducting further analysis. Empirical analysis shows that debt financing and equity financing has a significant impact on green accounting. However, the research findings show that profitability does not have a significant impact on green accounting. Despite equity financing being shown to enhance green accounting practices, highly profitable companies do not automatically increase their green accounting practices.